Alterations of neuroimmune cell density and pro-inflammatory cytokines in response to thimerosal in prefrontal lobe of male rats. (4th March 2019) - Afsordeh, Kobra; Sadeghi, Yousef; Amini, Abdollah; Namvarpour, Zahra; Abdollahifar, Mohammad-Amin; Abbaszadeh, Hojjat-Allah; Aliaghaei, Abass
Abstract: Evidence suggests that the effect of heavy metals on neuroimmune cells lead to neurogenic inflammatory responses. In this study, immune cells [mast cells (MCs) and microglia] and pro-neuroinflammation cytokines (interleukin-1b and tumor necrosis factor-α) were assessed in the prefrontal lobe of rat brains exposed to thimerosal in different timeframes. A total of 108 neonatal Wistar rats were divided into three groups having three subgroups. The experimental groups received a single dose of thimerosal (300 μg/kg) postnatally at 7, 9, 11, and 15 days. The vehicle groups received similar injections of phosphate-buffered saline in a similar manner. The control groups received nothing. Samples of the prefrontal cortex were collected and prepared for stereological, immunohistochemical, and molecular studies at timeframes of 12 or 48 h (acute phase) and 8 days (subchronic phase) after the last injection. The average density of the microglia and MCs increased significantly in the experimental groups. This increase was more evident in the 48 h group. At 8 days after the last injection, there was a significant decrease in the density of the MCs compared to the 12 and 48 h groups. Alterations in pro-inflammatory cytokines were significant for all timeframes. This increase was more evident in the 48 h group after the last injection. There was a significant decrease in both neuroinflammatory cytokines at 8 days after the last injection. It was found that ethylmercury caused abnormal neurogenic inflammatory reactions and alterations in the neuroimmune cells that remained for a longer period in the brain than in the blood.